Revitalizing The Role of Mosques To Improve The Economy Ummat Based Sharia In Medan City - Mhd Ilham Fauji; Yusrizal Yusrizal; Muhammad Ari Arif (Jurnal Ilmu Sosial Mamangan, 2024)
This research aims to find out how the strategy for revitalizing the role of mosques is to improve the sharia-based economy of the community in the city of Medan by presenting the internal and external conditions that have been carried out so far. Then, in addition, the researcher also explained several urgent measures that need to be implemented so that the revitalization of the role of mosques in improving the sharia-based economy of the community can be more focused. The method used is a qualitative method using SWOT and QSPM analysis. The number of respondents who filled out the questionnaire were 5 respondents each from MSME actors around the mosque and 5 respondents from experts. Based on the results of the SWOT analysis, the strategy quadrant obtained after processing it in the IFE and EFE matrices is in Quadrant I. This states that the strategy used is strategy progressive. Strategy This meaningful that revitalizing the role of mosques to improve the sharia-based economy of the ummah has strength and opportunity. Furthermore, in the QSPM analysis, the results showed that the main priority strategy that must be implemented is to utilize the provision of employment opportunities to increase the income and economy of the community.